On-chip testing of A/D and D/A converters:static linearity testing without statistically known stimulus - Korhonen, E. (Esa) (University of Oulu, 2010)
Abstract The static linearity testing of analog-to-digital and digital-to-analog converters (ADCs and DACs) has traditionally required test instruments with higher linearity and resolution than that of the device under test. In this thesis ways to test converters without expensive precision instruments are studied. A novel calculation algorithm for the ADC differential non-linearity (DNL) and integral non-linearity (INL) estimation is proposed. The algorithm assumes that two stimuli with constant offset between them are applied to the ADC under test and that the code density histograms for both stimuli are recorded. The probability density function (PDF) of the stimulus is then solved using simple calculations so that DNL and INL of the ADC can be estimated without a priori known stimuli. If a DAC is used to generate the stimulus to ADC, all inputs and outputs are digital and the new algorithm can be used to obtain the PDF of the DAC output. Moreover, the PDF of DAC actually characterizes its INL and DNL so that this all-digital test configuration enables a simultaneous testing of both converters thanks to the new algorithm.